2014
DOI: 10.1371/journal.ppat.1004359
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Vaccination and Immunity on Bacterial Infection Dynamics In Vivo

Abstract: Salmonella enterica infections are a significant global health issue, and development of vaccines against these bacteria requires an improved understanding of how vaccination affects the growth and spread of the bacteria within the host. We have combined in vivo tracking of molecularly tagged bacterial subpopulations with mathematical modelling to gain a novel insight into how different classes of vaccines and branches of the immune response protect against secondary Salmonella enterica infections of the mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 51 publications
1
54
0
Order By: Relevance
“…Both B and T cell responses are known to contribute to protection in mouse models of Salmonella infection and vaccination. While B cells can confer the first line of protection against mucosal invasion and systemic dissemination, T cells are needed for the efficient clearance of Salmonella 11 . In particular, CD4 + T cells play a major protective role in mouse models of S. Typhimurium infection 12 , with CD8 + T cells not essential for acquired immunity to this pathogen 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Both B and T cell responses are known to contribute to protection in mouse models of Salmonella infection and vaccination. While B cells can confer the first line of protection against mucosal invasion and systemic dissemination, T cells are needed for the efficient clearance of Salmonella 11 . In particular, CD4 + T cells play a major protective role in mouse models of S. Typhimurium infection 12 , with CD8 + T cells not essential for acquired immunity to this pathogen 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The migration is assumed to be constant over time in the model, however, previous research has shown that the number of bacteria in the blood exponentially decreases for iv inoculation. 99 Therefore, the migration we estimate to occur with a constant rate over one day, might have migrated only within the first few hours after inoculation. However, because we are not primarily interested in the migration rates themselves but rather the differences in migration rates between wildtype and knockout mice, this interpretational subtlety does not confound our conclusions.…”
Section: Population Dynamics Analysismentioning
confidence: 90%
“…Live attenuated vaccines saved countless lives and have helped to eradicate or control serious infectious diseases such as smallpox, measles, or polio . The advantages of live vaccines include easier application (eg, orally or nasally), the long‐term protection, and that booster injections are often dispensable . But what makes living microbes much more effective in comparison with their dead counterparts, and how does the immune system discriminate between live and inactivated vaccines?…”
Section: Role Of Microbial Rna In Vaccine Developmentmentioning
confidence: 99%